MEMBANGKITKAN BUDAYA SIAP SIAGA DARURAT MELALUI PELATIHAN PERTOLONGAN PERTAMA BAGI SISWA SEKOLAH DASAR - Bernike Burnama; Aurelia Naftali Kalengkongan; Mariani Angeline; Saula Rahmadianti K. Pertiwi; Novario Jaya Perdana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
ABSTRACT First aid is the immediate assistance given to individuals who suffer from injury or sudden illness, with the aim of saving lives, preventing the condition from worsening, and accelerating recovery. The ability to provide first aid (P3K) is a crucial basic skill in responding to emergencies. However, students’ knowledge and skills in administering first aid remain limited, resulting in suboptimal emergency responses. This community service (ABDIMAS) activity was designed and implemented to provide first aid training and introduce medicinal plants to students, specifically targeting fourth and fifth graders.The program consisted of educational sessions, hands-on practice, and planting medicinal plants. The hands-on component included treating injured peers and simulating emergency scenarios. To evaluate the success of the program, interviews were conducted with nine students using nine structured questions to assess their understanding and experiences after participating in the activity.The interview results revealed that all nine students understood the basic steps of first aid and were able to identify several types of medicinal plants along with their benefits. This activity is expected to raise students’ awareness of the importance of basic health knowledge and the simple use of natural resources. It also aims to build students’ confidence in their preparedness to respond to emergencies within the school environment.Through this educational approach, students are expected to be capable of administering first aid to themselves and their peers before professional medical help arrives, while also valuing and utilizing natural resources to support health. Additionally, the activity introduced various medicinal plants that can be used as part of natural healing efforts. ABSTRAK Pertolongan pertama merupakan bantuan segera yang diberikan kepada seseorang yang mengalami cedera atau sakit mendadak, dengan tujuan untuk menyelamatkan nyawa, mencegah kondisi memburuk, dan mempercepat pemulihan. Kemampuan memberikan pertolongan pertama (P3K) merupakan keterampilan dasar yang penting dalam menghadapi situasi darurat. Namun, pengetahuan dan keterampilan P3K pada siswa masih terbatas, sehingga respons terhadap keadaan darurat belum optimal. Kegiatan pengabdian kepada masyarakat (ABDIMAS) ini dirancang untuk memberikan pelatihan pertolongan pertama serta pengenalan tanaman obat kepada siswa kelas IV dan V. Program ini mencakup kegiatan sosialisasi, praktik langsung pertolongan pertama, serta penanaman tanaman obat. Praktik dilakukan melalui simulasi dan latihan mengobati teman yang mengalami luka ringan. Evaluasi keberhasilan program dilakukan melalui wawancara terhadap sembilan siswa dengan sembilan pertanyaan yang dirancang untuk mengukur pemahaman dan pengalaman setelah mengikuti kegiatan. Hasil wawancara menunjukkan bahwa seluruh siswa memahami langkah-langkah dasar pertolongan pertama serta dapat mengenali beberapa jenis tanaman obat beserta manfaatnya. Kegiatan ini diharapkan dapat meningkatkan kesadaran siswa akan pentingnya pengetahuan kesehatan dasar, mendorong pemanfaatan sumber daya alam secara sederhana, serta menumbuhkan kepercayaan diri dalam menghadapi keadaan darurat di lingkungan sekolah. Melalui pendekatan edukatif, siswa diharapkan mampu memberikan pertolongan pertama kepada diri sendiri maupun teman sebaya sebelum bantuan medis datang, serta menghargai kekayaan alam sebagai bagian dari upaya menjaga kesehatan.